2016
DOI: 10.1139/apnm-2016-0016
|View full text |Cite
|
Sign up to set email alerts
|

Lactate administration increases mRNA expression of PGC-1α and UCP3 in mouse skeletal muscle

Abstract: To examine the potential role of lactate as a signalling molecule in skeletal muscle, we performed global gene expression analysis of the mouse gastrocnemius muscle, 3 h after lactate administration using the Affymetrix GeneChip system (Affymetrix, Santa Clara, Calif., USA). Among the top 15 genes with the largest fold change, increased expression of Ppargc1a, Pdk4, and Ucp3 was confirmed using real-time quantitative polymerase chain reaction. Our findings suggest that lactate serves as a signal for upregulati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
62
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 71 publications
(67 citation statements)
references
References 20 publications
(19 reference statements)
5
62
0
Order By: Relevance
“…Accordingly, treatment with lactate elevated PGC‐1α mRNA in myotubes (Hashimoto et al . 2007) and mouse skeletal muscle (Kitaoka et al . 2016), and a restricted exercise‐induced decline in muscle pH blunted the PGC‐1α mRNA upregulation during the early recovery from high‐intensity exercise in humans (Edge et al .…”
Section: Discussionmentioning
confidence: 99%
“…Accordingly, treatment with lactate elevated PGC‐1α mRNA in myotubes (Hashimoto et al . 2007) and mouse skeletal muscle (Kitaoka et al . 2016), and a restricted exercise‐induced decline in muscle pH blunted the PGC‐1α mRNA upregulation during the early recovery from high‐intensity exercise in humans (Edge et al .…”
Section: Discussionmentioning
confidence: 99%
“…Citrate synthetase (CS), beta-HAD, and COXIV as well as the fatty acid transporter FAT/CD36 expression and protein content are increased with high-intensity interval training; however, when dichloroacetate was administrated (and lactate reduced), these adaptations were attenuated [50]. Moreover, PDK isoform 4 (which inhibits the conversion of lactate to pyruvate) and UCP3 (uncoupling protein 3, which improves mitochondrial oxidative capacity) were also increased with lactate administration in mouse muscle fibers—both proteins that are also upregulated by PGC-1 alpha [51]. …”
Section: Pgc-1 Alpha Mediates Lactate Adaptations In Muscle Fibersmentioning
confidence: 99%
“…Moreover, a recent study showed that in vivo lactate administration (by intraperitoneal injection on mice) upregulated PGC-1 alpha gene expression [51]. This clearly suggests that many possible lactate-induced adaptations are mediated by the upregulation of PGC-1 alpha.…”
Section: Pgc-1 Alpha Mediates Lactate Adaptations In Muscle Fibersmentioning
confidence: 99%
“…In vivo lactate administration increases messenger RNA levels of oxidative metabolism‐related genes as PGC‐1 α in skeletal muscle of mouse (Kitaoka et al. ). In skeletal muscle cell lines as L6 and C2C12, lactate activates the ERK1/2 pathway (Li et al.…”
Section: Introductionmentioning
confidence: 99%